Pelatihan Pembuatan Produk Kimia Rumah Tangga di MA Darul Habibi NW Paok Tawah Praya - Ratna Azizah Mashami; Dahlia Rosma Indah; Husnul Hatimah; Citra Ayu Deewi; Pahriah Pahriah (Jurnal Pengabdian UNDIKMA, 2020)
The purpose of this community service to provide an understanding that chemistry is fun, provide skills in making chemical products that are commonly used in everyday life, and increase student motivation in learning chemistry at MA Darul Habibi NW Paok Tawah Praya. The method used was demonstration, practice, and discussion, with training and mentoring approaches. Student responses to training were obtained from a questionnaire. The results of the questionnaire analysis showed 100% of students stated the material presented was easy to understand and the method used was fun, 90% of students stated that before training the chemistry lessons were not fun, 100% of students stated that chemistry lessons were fun after attending training, 83.3% of students were motivated to learning chemistry after attending training, 80% of students saw business opportunities and 73.3% of students wanted to try entrepreneurship through household chemical products. The training succeeded in changing students' views in a positive direction significantly.